The Impact of Liquidity and Digital Transformation on The Bank Performance: Board of Commissioners and Directors’ Turnover Moderator - Divia Maudy Ariesta; Yuli Soesetio (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Many banks are not achieving their full profit potential due to suboptimal management of their assets and capital.Purpose: This study seeks to investigate how liquidity and digital transformation (the independent variables) influence profitability (the dependent variable), with the frequency of changes in commissioners and directors acting as a moderating factor.Design/methodology/approach: The research analyzed 47 banks listed on the Indonesia Stock Exchange (IDX) from 2012 to 2022. These banks were selected through purposive sampling from the IDX and Financial Services Authority (FSA) websites. Pure moderation, Moderated Regression Analysis (MRA), and subgroup analysis were applied.Findings/Result: The study found that both liquidity and digital transformation positively impact profitability. Furthermore, changes in the leadership, specifically commissioners and directors, significantly influence this relationship.Conclusion: Liquidity and digital transformation plays a pivotal role in driving bank profitability. Additionally, the commissioners and directors turnover was found to moderate this relationship, indicating that leadership stability may enhance the benefits of these factors. This study contributes to the existing literature by providing empirical evidence from Indonesian banks, offering insights into how these variables interact to influence financial performance.Originality/value (State of the art): This study explores how banks listed on the IDX can boost their profitability by optimizing liquidity and applying digital transformation, considering the influence of leadership changes at the commissioner and director levels. Keywords: liquidity, digital transformation, bank profitability, commissioners turnover, director turnover